ANALISIS FAKTOR YANG MEMPENGARUHI MINAT BELI KONSUMEN TERHADAP PREFERENSI PEMBELIAN ANTARA PRODUK KOSMETIK RAMAH LINGKUNGAN DAN KONVENSIONAL - Pranoto, Alvin (Arthavidya Jurnal Ilmiah Ekonomi, 2017)
ABSTRACTA green product purchasing has already become a lifestyle nowadays. A Green product is better than convensional product because a green product deosn’t have a dangerous chemical for it’s produc.The example of a green product which will be explained is cosmetic. Cosmetic is the needed product everyday and everywhere. Everyone have different buying interest for green cosmetic product no matter woman or man need cosmetic everyday include models, teenagers, oldman. Especially in this new world cosmetic manifold green product is more interest than convensional product. At the time of developing era many people buy and choos the natural ones more than convensional, it isn’t seen from the result but it’s about naturally and safety. Supported by increasing advanced in information technology, make cosmetic not only sell for beauty but sell to care for the skin. Consumers can get many benefits if they buy a green product. Whitout additives and fresher when consumer use the green product, and if we see in different views convensional product is danger because people made them with preservatives and harmful ingredients which harm our body skin. That is what causes counsumers start to move and make decision to buying for green product than convensional product. Seen from consumer buying interest, consumer really care and racing to use natural cosmetic. They race to look attractive with green cosmetic product. Beside this if we buy a cosmetic product we have participated in the development of positive efforts made by the goverment.Keywords: green product, convensional product, cosmetic, buyinng interest